The management and conservation of rock art sites and paintings in the uKhahlamba-Drakensberg Park, KwaZulu-Natal, South Africa - Meiklejohn, K.I. (Ian) (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2012.